1995
DOI: 10.1093/ajcp/103.4.453
|View full text |Cite
|
Sign up to set email alerts
|

Gastric Carcinoma With Osteoclast-like Giant Cells:Report of Four Cases

Abstract: Four cases of gastric carcinoma are described that are associated with an osteoclast-like giant cell (OGC) stromal component. The patients were all middle-aged men (range 53-63 years). Microscopically, the tumors were characterized by a bland cytologic appearance, and an either solid or cribriform pattern. Osteoclast-like giant cells were found adjacent to, or intimately intermixed with, the neoplastic cells in the primary gastric masses and in the lymph nodal metastases and were often associated with lymphocy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
42
0

Year Published

1996
1996
2013
2013

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(45 citation statements)
references
References 0 publications
3
42
0
Order By: Relevance
“…The OGCs found in our patient had none of these characteristics. Similar to the reported cases of gastric carcinoma with OGCs (Baschinsky et al, 1999;Stracca-Pansa et al, 1995;Willems et al, 2005), the tumor invaded beyond the muscular layers in this case. There were 13 metastatic lymph nodes, and one of them was 3.5 cm in diameter.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…The OGCs found in our patient had none of these characteristics. Similar to the reported cases of gastric carcinoma with OGCs (Baschinsky et al, 1999;Stracca-Pansa et al, 1995;Willems et al, 2005), the tumor invaded beyond the muscular layers in this case. There were 13 metastatic lymph nodes, and one of them was 3.5 cm in diameter.…”
Section: Discussionsupporting
confidence: 90%
“…60 μm 60 μm 60 μm 60 μm gastric carcinoma with OGCs (Baschinsky et al, 1999;Stracca-Pansa et al, 1995;Willems et al, 2005), one case was immunohistochemical positive for LMP of the EBV (EBV-LMP) (Stracca-Pansa et al, 1995), while another case showed intense nuclear positivity for EBV measured by in situ hybridization (Willems et al, 2005). However, in this case, the immunohistochemical staining for EBV-LMP and in situ hybridization for EBV were non-reactive.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…Immunohistochemical staining for lysozyme, human defensin-5, and CDX2 is usually positive [204,205]. and (3) gastric carcinoma with osteoclast-like giant cells; these variants contains a minor component of giant cells that contain 3 to 20 nuclei and are positive for CD68 and vimentin [206]. These findings suggest that giant cells are of monocytic/ histiocytic origin and probably represent a host response to the tumor [207].…”
Section: Miscellaneous Carcinomasmentioning
confidence: 99%